Analisis Kelayakan Usaha UMKM Laundry “Seuseuhan” - Adriana Putri D; Nabila Nuzhatul F; Danish Nayyara Putri; Sikla Alfathlaily Suteja; Najwa Anjani Nurizkita; Antonya Rumondang Sinaga; Farida Ratna Dewi; Sari Heviawati; Novia Rahmawati (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
Small businesses play an important role in the Indonesian economy, including the service sector such as laundry, which requires good management to ensure sustainability and operational efficiency. This research was conducted on a laundry business located at Jl. Malabar Ujung No.34, RT.2/RW.07, Babakan, Bogor Tengah District, Bogor City, West Java. This research aims to analyze the financial feasibility of the laundry business "Seuseuhan Laundry" founded by Alfi Prasetya in Bogor City. The research method used is a quantitative approach with data collection techniques through direct interviews with the business owner. The analysis includes aspects of investment, operations, profit and loss, cash flow, as well as feasibility indicators such as Net Present Value (NPV), Internal Rate of Return (IRR), Profit on Sales, Break Even Point (BEP), Payback Period (PBP), and Benefit Cost Ratio (B/C). The analysis results show that this business is feasible to run, with a positive NPV, a payback period of 1,31 years, and a profit on sales of 14,04%. The break-even point is reached at revenue below the annual projection, indicating that the business has been able to cover costs since the first year. This study recommends optimizing digital promotions and improving service quality to expand the market and maintain customer satisfaction.